1985
DOI: 10.1080/09670878509370978
|View full text |Cite
|
Sign up to set email alerts
|

Problem of flower shedding caused by thrips,Megalurothrips distalis(Karny), on summer mungbean,Vigna radiata(L.) Wilczek, and its control

Abstract: Flower shedding in summer mungbean, Vigna radiata (L.) Wilczek, is a common feature caused by thrips, Megalurothrips distalis (Karny). Eleven insecticides were tested in field trials for the control of thrips during the period 1982 to 1984. All the treatments were significantly better in controlling the thrips, reducing flower shedding, increasing the pod numbers and grain yield, in comparison with the control. Increases in yield compared with the control during trials ranged from 85 to 89% (1982), 26 to 96% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Overall, dimethoate was still the most effective treatment providing 55.74 to 84.92% reduction up to 7 DAT but with decreasing efficacy over the days as was the case for all the treatments. Earlier, Chhabra and Kooner (1985b) reported that dimethoate gave a high control of thrips in mung bean in Punjab. HMOs also reduced the insect population with 41.16-77.78%, while pongamia soap was the least effective (8.16-44.18%) among all botanicals although it was significantly better than water spray alone and untreated control.…”
Section: Reduction Percentagementioning
confidence: 96%
See 1 more Smart Citation
“…Overall, dimethoate was still the most effective treatment providing 55.74 to 84.92% reduction up to 7 DAT but with decreasing efficacy over the days as was the case for all the treatments. Earlier, Chhabra and Kooner (1985b) reported that dimethoate gave a high control of thrips in mung bean in Punjab. HMOs also reduced the insect population with 41.16-77.78%, while pongamia soap was the least effective (8.16-44.18%) among all botanicals although it was significantly better than water spray alone and untreated control.…”
Section: Reduction Percentagementioning
confidence: 96%
“…In 2019, treatment with homemade neem extracts (boiled and overnight soaking) resulted in a yield of 1210 and 1102 Kg ha −1 , respectively, to get 40.37 and 27.9% increase in yield over untreated control. Chhabra and Kooner (1985b) reported that dimethoate gave a high control of thrips in mung bean at Ludhiana and increased the yield with up to 89%. Horticultural mineral oils MAK All Season and Arbofine were less effective than botanicals as they led to only 14.50 and 24.25% increase in yield over untreated control, respectively (Table 4).…”
Section: Yield and Percent Increase In Yield Over Untreated Controlmentioning
confidence: 99%
“…The three major genera that comprise this group all involve species that breed mainly in the flowers of Fabaceae. Species in two of them, Odontothrips and the Australian genus Odontothripiella, are rarely associated with crop plants, whereas several species of Megalurothrips are important as pests of bean crops in tropical and subtropical countries [57][58][59]. Two further genera that are possibly related to this genus-group are Ceratothripoides and Pezothrips [37].…”
Section: Megalurothrips Genus-groupmentioning
confidence: 99%
“…Several insect pests have been reported to infest mungbean and damage the seedlings, leaves, stems, flowers, buds, pods causing considerable losses [7,8,9]. The most damaging insect pests of mungbean recorded so far are stemfly [10,11], jassid [12,13], whitefly [14,15], thrips [14,16], hairy caterpillar [14] and pod borer [14,17]. Stemfly attack mainly the crop by feeding on tender stems at seedling stage, although it may attack at any stage of the crop.…”
Section: Introductionmentioning
confidence: 99%
“…Thrips is associated mostly with the damage of tender buds and flowers of mungbean [11]. Chhabra and Kooner [16] have reported extensive damage to the summer mungbean due to flower shedding caused by thrips.…”
Section: Introductionmentioning
confidence: 99%